The US Initiative on Creating an Environment for Nuclear Disarmament - Kurosawa, Mitsuru (Journal for Peace and Nuclear Disarmament, 2020)
The purpose of this paper is to examine and critically evaluate a new US initiative called Creating an Environment for Nuclear Disarmament (CEND), which was launched in 2018. CEND's main argument is that in order to achieve nuclear disarmament it is necessary to improve the international security environment considering a geopolitical point of view. The research question here is "Is CEND useful for promoting nuclear disarmament or for providing a pretext for not working for nuclear disarmament?" First, this paper will introduce the US proposals on this initiative to understand clearly and precisely its contents and intentions, and then survey the argument at the Preparatory Committee for the NPT Review Conference in 2019 to understand well the arguments for and against the new initiative. In the third section, two meetings for the CEND held in 2019 will be introduced. The fourth section will precisely analyze the contents of CEND's arguments using the following four criteria: (i) the relationship between nuclear disarmament and security; (ii) the relationship between nuclear disarmament and nuclear non-proliferation; (iii) the abandonment of the step-by-step approach; and, (iv) the abandonment of the undertakings of the previous NPT review conferences. The fifth section will consist of an evaluation of the contents of the new initiative by some experts. Finally, this paper will conclude with a critical analysis of the initiative and recommend pursuing nuclear disarmament and security simultaneously.